2019
DOI: 10.4103/joacp.joacp_195_18
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter survey on the use of neuromuscular blockade in Greece. Does the real-world clinical practice indicate the necessity of guidelines?

Abstract: Background and Aims: The aim of this study was to investigate the current status of clinical practice regarding neuromuscular blocking drugs and their antagonists in Greece. Material and Methods: This is a multicenter survey, including a questionnaire based on previous studies, which was translated and modified by a Task Force of the Hellenic Society of Anaesthesiology. It was completed on a web-based database after invitation via e-mail and was left online for a period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Other publications have found that 75% of Danish anesthesiologists reported technical problems when using these devices, accounting for 25% of anesthesia equipment [29]. Batistaki et al reported that 60% of respondents stated that the devices for monitoring the degree of skeletal muscle relaxation should be minimal in the anesthesia workstation [30]. Cyclically implemented recommendations in Great Britain have resulted in a significant increase in the frequency of monitoring the degree of relaxation, from 9 to 31%, and a reduction in the number of respondents who did not routinely use this method, from 62 to 8.9% [13,[31][32][33][34].…”
Section: Professional Perspectivesmentioning
confidence: 99%
“…Other publications have found that 75% of Danish anesthesiologists reported technical problems when using these devices, accounting for 25% of anesthesia equipment [29]. Batistaki et al reported that 60% of respondents stated that the devices for monitoring the degree of skeletal muscle relaxation should be minimal in the anesthesia workstation [30]. Cyclically implemented recommendations in Great Britain have resulted in a significant increase in the frequency of monitoring the degree of relaxation, from 9 to 31%, and a reduction in the number of respondents who did not routinely use this method, from 62 to 8.9% [13,[31][32][33][34].…”
Section: Professional Perspectivesmentioning
confidence: 99%
“…However, equipment alone is not enough; repeated educational efforts as part of a quality assurance program are mandatory [ 60 ]. Education of clinicians and other anesthesia providers on outcomes of untreated residual neuromuscular blockade [ 61 ], monitoring with indicators such as the use of neuromuscular monitoring whenever neuromuscular blockers are used, documenting and using the results to motivate anesthesia providers to pursue the trend, and elaborating clear protocols in the use of different antagonists would help to decrease the incidence of complications.…”
Section: Implementation Of Neuromuscular Monitoring Culturementioning
confidence: 99%
“…The present study assumes national rates of procedures using NMB and market shares of NMBAs and reversal agents, based on unpublished data and surveys, due to a lack of published information. NMB and NMB reversal practice may vary by patient, procedure, and provider, with significant variability within the US and across countries, as evidenced by the lack of international guidelines [73][74][75][76]. Hence, the findings need to be interpreted with care for smaller geographical regions, potential temporal change in these estimates, and varying local practice [74].…”
Section: Limitationsmentioning
confidence: 99%